Organic farming: an ecofriendly way to sustainable agriculture - Mandal, Daya N. (Journal of Agriculture and Environment, 2007)
Organic farm products have got more value as compared to inorganic products. People are becoming more conscious for their health and environment. Bio-farming is sustainable and eco-friendly which enables to conserve biodiversity and to protect environment. Organic farming system avoids or largely excludes the use of synthetically compounded fertilizers, pesticides, growth regulators, and livestock feed additives. It mainly relies upon crop rotation, organic manures, bio-pesticides and integrated pest management (IPM). In this paper emphasis has been given to practice in favors of organic farming, bio-pesticides, and preparation and use of organic manures by different methods in a hygienic manner. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 115-118